2023
DOI: 10.1093/ecco-jcc/jjac190.0008
|View full text |Cite
|
Sign up to set email alerts
|

OP08 Mucosal healing with vedolizumab in inflammatory bowel disease patients with chronic pouchitis: Evidence from EARNEST, a randomized, double-blind, placebo-controlled trial

Abstract: Background Mucosal healing (MH) is an important treatment goal for inflammatory bowel disease (IBD). Vedolizumab (VDZ), a gut-selective anti-lymphocyte trafficking agent, has shown potential to achieve MH.1,2 EARNEST, a randomized double-blind placebo-controlled trial of VDZ in chronic pouchitis,3 offers a robust dataset systematically collected from the inflamed pouch mucosa to further explore the impact of VDZ treatment on MH. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In the EARNEST trial, vedolizumab led to a higher proportion of patients with reduction in ulcers/erosions in the pouch, ulcerated surface area and endoscopic mucosal healing as measured by the SES‐CD score and histological remission. Furthermore, achieving mucosal healing at week 14 was associated with a higher likelihood of clinical remission and improved quality of life at week 34 6 …”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In the EARNEST trial, vedolizumab led to a higher proportion of patients with reduction in ulcers/erosions in the pouch, ulcerated surface area and endoscopic mucosal healing as measured by the SES‐CD score and histological remission. Furthermore, achieving mucosal healing at week 14 was associated with a higher likelihood of clinical remission and improved quality of life at week 34 6 …”
Section: Discussionmentioning
confidence: 96%
“…In 2022, the results of the EARNEST trial were presented. 6,7 This was a phase 4, randomised placebocontrolled trial of vedolizumab in patients with active chronic pouchitis and demonstrated the benefit of vedolizumab across a range of endpoints (clinical, endoscopic and histological). Despite the relatively small sample size, reflective of the orphan nature of this indication, the EARNEST trial led to the approval of vedolizumab for chronic pouchitis by the European Medicines Agency.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations